A digital transformation in Kenya bringing farmers closer to seedling producers - Coyne, D.L.; Kisaakye, James; Nyambura, Eva Ivy; Miringu, Newton Nyagah; Odera, Janet Achieng; Njeri, Ann; Irungu, Miriam; Awino, Martha; Claereboudt, Etienne; Murithi, Harun; Nyabuto, Mellen; Mwenda, Godfrey (CGIAR System Organization, 2025)
The OnLima platform involves the use of a USSD code (*789*7892#) that works offline using android mobile phones by accessing the service via text prompts. Growers can then access various information, such as the availability, price, variety and locality of seedlings, with which propagators, across the country. It was developed by PremaGrow seedling propagators in collaboration with the International Institute of Tropical Agriculture (IITA) and the International Potato Center (CIP). It aims at linking farmers to seedling producers, improving access to quality planting material in a highly convenient and affordable way